CHARACTERISTICS OF miRNA INTERACTION WITH mRNA OF ISCHEMIC HEART DISEASE CANDIDATE GENES - Mukushkina Dina Daurenbekovna,; Siegfried Labeit,; Ivashchenko Anatoliy Timofeevich, (Academic Journal of Physical and Chemical Sciences, 2021)
Ischemic heart disease (IHD) is the most serious cardiovascular disease and one of the leading causes of death worldwide. An important role in the pathophysiology of IHD play such processes as the processes of inflammation and immune response, metabolism of homocysteine and folate, development processes of endothelial dysfunction and oxidative stress and homeostasis system. Accordingly, the identified genes that are directly involved in these processes. In addition, miRNA (mRNA-inhibiting RNA) may affect the expression of these candidate genes. Using bioinformatics methods, the most efficient associations of miRNA and target genes were established. This research presents the characteristics of miRNA interactions with mRNA of candidate IHD genes. Candidate genes were identified that had a free energy of interaction with miRNA equal to -120 kJ / mole and higher in the following interactions: in 5’UTR - ALDH2 and ID02142.3p-miR; CELSR2 and ID00457.3p-miR; DDAH2 and ID01272.3p-miR; DNMT1 and ID02052.5p-miR; DOCK7 and ID00061.3p-miR; EGFR and ID02457.3p-miR; FOLH1 and ID01428.3p-miR; IL6R and miR-6089; NOS3 and ID02363.5p-miR; NPC1 and ID00551.3p-miR; PPP1R17 and ID01693.5p-miR; PRKCH and ID00520.5p-miR; SERPINE1 and ID01098.3p-miR; in CDS - ABCG8 and ID03064.3p-miR; ADORA2A and ID02697.3p-miR; APOA1 and ID00457.3p-miR; CDKN2B and ID02899.3p-miR; IL6R and ID01806.3p-miR; TIMP2 and ID00098.5p-miR; TNF and ID02050.3p-miR; TRIB1 and ID03208.5p-miR; VWF and ID01238.5p-miR. Associations were also revealed in the 3'UTR region with an interaction free energy of - 115 kJ/mole and higher: AGTR2 and ID01213.5p-miR; APLNR and ID00616.5p-miR; CXCL12 and ID00483.3p-miR; FADS2 and miR-1224-3p; FCGR2A and miR-1273g-3p; GCKR and ID02928.3p-miR; IL6R and ID00913.5p-miR; KCNJ11 and ID03288.5p-miR; PPP1R3B and ID00913.5p-miR; TFPI and miR-1273g-3p; TIMP2 and ID01941.5p-miR. The results obtained could be used as molecular genetic markers of IHD for the diagnosis of this disease.